(untitled) (International Journal of Engineering and Computer Science, 2017)
The objective of this paper is to design and develop a video surveillance and monitoring system that will provide easy access to both live and archived images during and after an institutions examination. My motivation into this paper work is the rate at which students and staff of tertiary institutions participate and encourage examination malpractice. The paper methodology adopted for this paper work was by observation. The top-down software design was adopted for this research. Prototype development methodology was used in the development of the system and Microsoft visual studio 2010; using visual basic in the .net framework was used as the programming language. The resultant outcome of this paper was tested to make sure examination malpractice in tertiary institutions is brought to its lowest minimum, making sure all requirements are met and are working perfectly as expected, bringing all offenders and defaulters involved in examination malpractice to book.